THE ROLE OF PHYSICAL EDUCATION IN THE EDUCATION OF STUDENTS TASHKENT INSTITUTE OF FINANCE - F. Kh. Karimov (Journals Park Publishing, 2022)
Pupils' physical culture is an important factor determining the effectiveness of physical education. Also, physical culture is an integral part of the general culture of man and society.
Keywords: physical training, mental, moral and aesthetic training, sports games, action games, agility.